Passivation of silicon surface by ultrathin dielectric film in M/Si/nematic/ITO structures - Gritsenko, M.I.; Kucheev, S.I.; Lytvyn, P.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
In this work the experimental observation of passivation of silicon surface by ultrathin dielectric film in Al/Si/nematic/Indium Tin Oxide(ITO) structure performed on the base of low resistive (~ several Ωxcm) n-type conductivity silicon sample is presented. It is shown that when the DC voltage with polarity +U on silicon is applied to the structure a passivation effect of silicon surface takes place. It is found that a silicon surface passivated by dielectric film changes an initial alignment of liquid crystal 5CB. In the structure with passivating silicon surface a frequency range of structure photosensitivity extends due to limitation of current leakage through Si/liquid crystal interface.
Keywords: nematic, silicon, passivation, alignment, photosensitivity, light modulator.